Phototherapy for neonatal jaundice at distances of 20 cm vs 40 cm - Winra Pratita; Supriatmo Supriatmo; Guslihan Dasa Tjipta (Paediatrica Indonesiana, 2013)
Background Neonatal jaundice is one of the most common problems in newborns. Phototherapy is the most widespread treatment for lowering bilirubin concentration in neonates. Phototherapy may be more effective if the light source is placed closer to the neonate.Objective To compare the effectiveness of phototherapy with a 20 cm distance between the light source and the neonate vs a 40 cm distance for decreasing serum bilirubin concentrationMethods An open, randomized, controlled trial was conducted at H. Adam Malik and Pirngadi Hospitals in Medan from August 2009 to March 2010. Subjects were divided into two groups. One group (n=30) received phototherapy at a distance of 20 cm between the light source and the neonate, while the other group (n=30) received phototherapy at a distance of 40 cm. The inclusion criteria in the study were newborns presenting with neonatal jaundice in their first week of life. Serum bilirubin levels were measured at baseline, as well as after 12 hours and 24 hours of phototherapy.Results The mean total bilirubin levels of the 20 cm and 40 cm groups at baseline were 18.8 (SD 1.73) mg/dL and 17.7 (SD 1.46) mg/dL, respectively, not significantly different. After 24 hours of phototherapy, the mean decreases in total serum bilirubin levels of the 20 cm and 40 cm groups were significantly different with 7.6 (SD 1.01) mg/dL and 2.0 (SD 0.83) mg/dL, respectively, (P<0.05).Conclusion Phototherapy with a 20 cm distance between the light source and the neonate is more effective than a 40 cm distance for decreasing bilirubin levels at 24 hours in newborns with hyperbilirubinemia.